Implementation of Kindergarten Supervisor Academic Supervision - Erna Kusumawati (International Journal of Social Service and Research, 2023)
Study This aim For analyse the implementation of supervision academic done by supervisor Kindergarten in East Jakarta. Method which is used in this research is a descriptive qualitative approach. Research design using studies case Which will conducted in one of the Kindergartens in East Jakarta. Results study shows that: (1) Implementation of supervision academic by the supervisor school has fulfil principle supervision implementation academic done with technique supervision individual And group; (2) Act carry on supervision academic by supervisor Kindergarten by providing reinforcement to teachers who have fulfil competency standards and coaching to Teacher which has not been fulfil competency standards.